Hydrogel-based magnetoelectric microenvironments for tissue stimulation - Hermenegildo, B. (2019)
The development of strategies to mimic the natural environment of tissues with engineered scaffolds remains one of the biggest challenges of tissue engineering. Hydrogels appear as suitable materials for this purpose due to their substantial water content, biocompatibility, and for being able to carry nanomaterials that introduce new functionalities to the hydrogel. The incorporation of magnetically responsive and, in particular, magnetoelectric materials into the hydrogel-based scaffolds are a promising approach for bone tissue engineering applications once it can promote not only tissue regeneration through magnetic to mechanic to electrical conversion/stimuli but also the external control of the scaffold by the application of magnetic fields. This work reports on a new CoFe2O4/ Methacrylated Gellan Gum (GGMA)/poly(vinylidene fluoride) (PVDF) hydrogel-based scaffold with 20kPa Young's modulus and cell viability superior to 80%. The 1µm thick PVDF/CoFe2O4 spheres added to GGMA gel (2wt.%) exhibit 20emu.g-1 magnetization saturation, 2.7kOe magnetic coercivity and -phase contents 78%, leading to a piezoelectric response |d33| of 22 pC N-1 and a magnetoelectric response of |d33| 6 pC N-1 at a DC magnetic field of 220mT, as verified for the CoFe2O4/PVDF spheres with 20wt.% filler content. Such characteristics allow novel tissue regeneration strategies approaches once CoFe2O4/GGMA/PVDF has a porous 3-D structure, biocompatibility, bioresorbability, and mechanical/electrical dynamic responses that can be triggered by an applied external magnetic field.